CONDITIONAL MOMENTS OF THE DISTANCE DISTRIBUTION TWO RANDOM POINTS IN A CONVEX DOMAIN IN R ^2 - Aramyan, R.H.; Mnatsakanyan, V.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2020)
In this article we define two new integral geometric concepts: conditional moments of the chord length distribution of a convex domain and conditional moments of the distance distribution of two independent uniformly distributed points in a convex domain. We also found a relation between these two concepts.